Parental Punishment and Adolescents’ Loneliness: A Moderated Mediation Model of General Self-Concept and Teacher–Student Relationships - Luo, Yun; Wu, Anyi; Zhang, Hui (Frontiers in Psychology, 2021)
Background: Loneliness adversely affects physical and mental health; therefore, it is necessary to explore its related influencing factors and mechanisms. This study investigated the mediating role of general self-concept in the association between parental punishment (PP) and adolescent loneliness and as well as the moderating role of teacher–student relationships (TSR) in Chinese students. Methods: Data were obtained from 1,169 Chinese students (10–18years old) using several self-report questionnaires: the Egna Minnen av Barndoms Uppfostran (EMBU), Self-Description Questionnaire (SDQ), Teacher–Student Relationships Scale (TSR), and UCLA Loneliness Scale. Data were analyzed with IBM SPSS 22.0, and the PROCESS macro program. Results: (1) Parental punishment had a positive predictive effect on adolescent loneliness, (2) parental punishment predicted adolescent loneliness not only directly but also indirectly through the mediating effect of general self-concept, and (3) teacher–student relationships moderated the influence of PP on adolescent loneliness. Conclusion: Adolescent loneliness is less affected by parental punishment when TSRs are better. Additionally, when adolescents are punished less by their parents and have good teacher–student relationships, they have higher general self-concepts. Limitations: This study’s cross-sectional research design was unable to show causal relationships among the factors influencing adolescent loneliness.